Saint Lucia. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Saint Lucia during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as beekeeping, technology, family farming, exports, trade, governance, public policies, sustainability and food security. . Finally, support was given to young entrepreneurs, the value chains of honey, pollen and small and medium-sized companies.